A cultural approach to interpersonal communication : essential readings - Goodman, Jane E. , 1956-; Monaghan, Leila Frances , 1960-; Robinson, Jennifer Meta , 1962- (Malden, Massachusetts : Wiley-Blackwell, 2012)
"The Second Edition of A Cultural Approach to Interpersonal Communication presents key readings from the fields of cultural and linguistic anthropology, sociolinguistics, and communication studies that explore the ways that interpersonal communication is socially and culturally mediated. Starting from the premise that interpersonal communication is inseparable from culture, the readings reveal the rich diversity of communicative practices of social communities within the U.S. and around the world. The fully-revised second edition features several new chapters that highlight interpersonal communication in a digital world, covering such topics as situated engagements with social media, text messaging, digitally simulated spaces, television, and public video-sharing sites. Other readings explore interpersonal interactions in wide-ranging settings that include high school slang in California, sports talk in New Zealand, Tuareg greetings in the Sahara Desert, avatar-mediated conversations in Second Life, frat talk at a Midwest college, whispered rumors about Nevada's top-secret Area 51, and many more. In addition, a variety of ethnographic case studies serve to heighten awareness of the reader's own interpersonal language practices. A Cultural Approach to Interpersonal Communication, 2nd Edition, provides rich insights into the crucial role of culture in shaping our understanding of interpersonal communication. "
1. Ethnographer's toolkit -- 2. Applying the ethnographer's Toolkit -- 3. Ethnography of talk : from language form to social solidarity -- 4. Communication and social groups : the work of belonging -- 5. Interpersonal communication in institutional settings : structure, agency, and the exercise of power
Includes bibliographical references (p. [468]-471) and index
Keywords: Communication and culture; Interpersonal communication -- Cross-cultural studies; Language and culture